Analysis of the process towards the co-partnership in the sub basin of the river Aguas Calientes, district of Madriz, Nicaragua - Pérez Carrasco, René R. (2006)
Tesis (M. Sc) -- CATIE, Turrialba (Costa Rica), 2006